The Relationship Between Peer Attachment and Self Regulated Learning in Working Students: Hubungan Antara Peer Attachment dengan Self Regulated Learning pada Mahasiswa Pekerja - Adhim, Muhammad Rozaqul; Laili, Nurfi (Indonesian Journal of Innovation Studies, 2023)
This research is motivated by the phenomenon of the gap between students and working students, where working students have low Self-Regulated Learning. This study aims to determine the relationship between Peer Attachment and Self Regulated Learning of student workers. Using a quantitative method conducted at University X with a sample of 323 working students with a sampling technique of Probability Simple Random Sampling. Data collection uses 2 psychological scales, namely, the Peer Attachment scale with 18 valid reliability items of 0.901 and the Self Regulated Learning scale with 43 valid reliability items of 0.930. The results of the analysis obtained a correlation coefficient (rxy) of 0.987 with a significance value of 0.000 <0.05. There is a positive relationship between Peer Attachment and Self Regulated Learning in working students, the higher Peer Attachment the higher Self Regulated Learning in working students at University X. On the other hand, the lower Peer Attachment, the lower Self Regulated Learning in working students at University X. Variable X gives a contribution of 97.5% to the Y variable.